STRATEGI PEMULIHAN AIR PASCATAMBANG BATUBARA BERBASIS EKONOMI SIRKULAR DAN POTENSINYA UNTUK BUDIDAYA IKAN DENGAN RECIRCULATING AQUACULTURE SYSTEM (RAS) : A SYSTEMATIC LITERATURE REVIEW - Yulius Kisworo; Rina Iskandar; Bahrun; Frans Toni; Rozzana Erziaty (Fakultas Pertanian UVAYA Banjarmasin, 2026)
Coal post-mining water represents a major environmental challenge due to its low pH and elevated concentrations of dissolved metals, particularly iron (Fe) and manganese (Mn). However, within a circular economy framework, post- mining water can be recovered and reused as a valuable resource. This study aimed to identify, evaluate, and synthesize resource recovery strategies for coal post-mining water and assess their potential application in Recirculating Aquaculture Systems (RAS). A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. The literature search identified 90 records, and after a rigorous screening process, 23 articles met the inclusion criteria and were included in the qualitative synthesis. The results showed that phytoremediation, bioremediation, constructed wetlands, electrocoagulation, and biosorbents effectively improved water quality by increasing pH and reducing Fe and Mn concentrations. Furthermore, the biological treatment mechanisms applied in these technologies were conceptually compatible with the biofiltration processes used in RAS. The integration of mine water reuse, aquaponics, nutrient recovery, and waste utilization demonstrated strong potential to support circular economy practices. Overall, recovered coal post-mining water showed considerable potential as an alternative water source for RAS, although further technical and biological validation is required before large-scale implementation